2005
DOI: 10.1021/es040474o
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Selective Adsorption of Amino Acids by Components of Natural Sediments

Abstract: We present evidence that under circumstances of low pH and organic-free surfaces an ordinary estuarine sediment can exhibit strong optical isomer selectivity in its absorption of a number of amino acids. This selectivity can also be seen to a lesser degree in the minerals quartz, montmorillonite, and kaolin. Adsorption reactions were performed with racemic amino acid mixtures, and after equilibrium, deviations from a D/L ratio of 1 were measured and in many cases were found to be significant. This was particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 24 publications
1
15
1
Order By: Relevance
“…Thus, questions remain as to whether soil components assemblages are net "isomer-blind" at the macro-scale in their sorption of chiral compounds or whether chiral constituents, e.g. L-amino acids forming proteins, D-ribose and D-deoxyribose units forming ribonucleic acid (RNA) and deoxyribonucleic acid (DNA), or even chiral minerals [20,22], could lead to the enantioselectivity that is evident in biological systems [23].…”
Section: Optical Isomers or Enantiomers Have Practically Identical Chmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, questions remain as to whether soil components assemblages are net "isomer-blind" at the macro-scale in their sorption of chiral compounds or whether chiral constituents, e.g. L-amino acids forming proteins, D-ribose and D-deoxyribose units forming ribonucleic acid (RNA) and deoxyribonucleic acid (DNA), or even chiral minerals [20,22], could lead to the enantioselectivity that is evident in biological systems [23].…”
Section: Optical Isomers or Enantiomers Have Practically Identical Chmentioning
confidence: 99%
“…In this regard, although several authors have reported results of batch sorption experiments where different chiral compounds seemed to exhibit strong enantioselectivity in their sorption on natural soil and sediment materials [23][24][25], others have failed to identify sorption enantioselectivity [21,[26][27][28]. Since sorption is a key process determining the amount of pesticide available for other transport and degradation processes, enantioselective sorption to chiral soil, sediment, or aquatic components would greatly affect the fate of chiral pesticides in the environment by making one of the enantiomers more available than the other [2,9,17].…”
Section: Optical Isomers or Enantiomers Have Practically Identical Chmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, enantioselective sorption to chiral clays or chiral soil, sediment, or aquatic organic matter could affect the fate of chiral compounds in the environment (29 ).…”
Section: Future Research Opportunitiesmentioning
confidence: 99%
“…Even though the ability of certain soil components with chiral crystalline structures (quartz) or chiral surface properties (calcite) to enantioselectively adsorb different chiral compounds was reported long ago (Bonner and Kavasmaneck, 1976;Hazen et al, 2001), the enantioselectivity of pesticide sorption in soil is difficult to identify and predict due to the heterogeneity and complexity of organomineral soil colloids and also to the fact that the different enantiomeric morphologies of soil components can be equally abundant (Frondel, 1978, Matallo et al, 1998. Thus, questions remain as to whether soil components assemblages are net "isomer-blind" at the macro-scale or whether inherent selectivity could lead to the homochirality that is evident in biological systems (Wedyan and Preston, 2005). In this regard, many biological structures are chiral and, consequently, are good candidates to display a chiral preference.…”
Section: Introductionmentioning
confidence: 99%